Design and implementation of a three dimensions (3D) printer for modeling and pre-manufacturing applications - Ghazi Qaryouti; Abdel Rahman Salbad; Sohaib A. Tamimi; Anwar Almofleh; Wael A. Salah; Qazem Jaber (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The three-dimensional (3D) printing technologies represent a revolution in the manufacturing sector due to their unique characteristics. These printers arecapable to increase the productivitywithlower complexity in addition tothe reduction inmaterial waste as well the overall design cost prior large scalemanufacturing.However, the applications of 3D printing technologies for the manufacture of functional components or devices remain an almost unexplored field due to their high complexity. In this paper the development of 3D printing technologies for the manufacture of functional parts and devices for different applications is presented. The use of 3D printing technologies in these applicationsis widelyused in modelingdevices usually involves expensive materials such as ceramics or compounds. The recent advances in the implementation of 3D printing with the use of environmental friendly materialsin addition to the advantages ofhighperformance and flexibility. The design and implementation of relatively low-cost and efficient 3D printer is presented. The developed prototype was successfully operated with satisfactory operated as shown from the printed samples shown.